Intestinal parasitism in a population of 1 to 10 years - César Pérez Martínez; Amanda Rodriguez Toribio; Lázaro Yoan Ordóñez Álvarez; Víctor Corrales Aguilar; Amarilis Fleita Rodriguez (Universidad Médica Pinareña, 2018)
Introduction: diseases caused by intestinal parasites are a serious health problem in children. Objective: to characterize the intestinal parasitism in the population between one and ten years of the community attended by the medical clinic No. 2 of the Pedro Borras Astorga Polyclinic, during the year 2017. Method: an observational, descriptive and transversal study was carried out. The universe consisted of 123 children, selecting a sample of 57. A bibliographic review of materials and sources was made on the different aspects treated in the research and the documentary analysis of the individual clinical histories; In addition, a data collection form was prepared, based on the medical interview. All variables were given an absolute and relative percentage frequency distribution. Results: male sex prevailed (54,4 %) and the age group between six and ten years old (51,2 %). Giardia lamblia was the main intestinal parasite (43,9 %). Abdominal pain was the main clinical manifestation (49,1 %). 70,2 % of the patients were normal weight. 38,6 % washed their hands before eating and 43,9 % after defecating. 42,1 % washed the food before ingesting it. 71,9 % drink treated water. The treatment of choice was effective in 61,4 % of the patients. Conclusions:the actions of prevention of health by the basic work team contribute to diminish the incidence of intestinal parasitism in the infantile population.